Cretaceous–Cenozoic sedimentary budgets of the Southern Mozambique Basin: Implications for uplift history of the South African Plateau. (September 2015) - Said, Aymen; Moder, Christoph; Clark, Stuart; Ghorbal, Badr
Highlights: Sedimentary budgets in the Southern Mozambique Basin. Uplift history of the South African Plateau. Two major periods of high sedimentation rates: the first, of Mid–Late Cretaceous age, and the second of Miocene age. The Miocene high sedimentation is likely related to an uplift of the source area. Abstract: In this study, data from 41 wells were used to quantify the evolution of the sedimentary budget in the Southern Mozambique passive margin basin, with a high temporal resolution for the Cenozoic period. We found that the drainage areas, which supplied sediments to the Southern Mozambique Basin, were eroded in two episodes. The first, of Mid–Late Cretaceous in age, is concordant with both thermochronological datation and sedimentary fluxes estimated by other studies in the Namibian and South African and Northern Mozambique margins. This erosion episode ended when the African surface, as defined by Burke and Gunnel (2008), had become flat and low-lying over most of the South African Plateau by ∼65 Ma. Carbonate sediment deposition became more important in the shallow waters of the Mozambique basin after that time. The second erosion episode began at ∼23 Ma and is likely due to an uplift event of the North-eastern part of the South African Plateau. It seems that the Limpopo catchment and the whole area sourcing the studied basin have inherited their present relief from two epeirogenic uplift pulses of Late Cretaceous and Miocene ages.